Ks. prof. Jan Decyk jako liturgista - Krzysztof Filipowicz (Studia Theologica Varsaviensia)
This article is dedicated to Prof. F. Jan Decyk who suddenly past away. He was a priest of the Diocese of Plock. As a theologian of liturgy in his research and teaching activities he was bound with the environment of Cardinal Stefan Wyszynski University in Warsaw. From 1999 to 2005 Prof. F. Jan Decyk was the vice-dean of the Faculty of Theology of this University and in the years 1996-2015 he was the head of the Department of History of Liturgy. About 85 works including 10 dissertation were created under his direction. In his theological research he focused on the cult of the dead in renewed liturgy after Vatican Council II. These studies were the part of contemporary eschatology. The last part of the article, written by a student and professor’s assistant, is kind of memory devoted to the friendliness that late prof. f. Jan Decyk showed to his students during his priestly and academic work.